Discriminations : égalité, reconnaissance et retours du refoulé - François Dubet (Socio, 2014)
The experience of discrimination does not depend uniquely on the intensity of the discrimination suffered: it also depends on it being embedded in social inequalities and on the conceptions which people have of social justice. This experience is further sharpened by the fact that people adhere to the meritocracy of equality of opportunity. But those who suffer discrimination demand both equitable equality of treatment and a recognition of the dignity of the identities which are the source of the discrimination. This dual rationale does not have the same consequences on the majority society: the struggle for equality is in line with the meritocracy model of the majority whereas the demand for recognition creates difficulties for the dominant conceptions of ‘nature’ and the nation which are the basis of the framework of ordinary social life.